Acute radiology rarely confirms sinus disease in suspected recurrent acute rhinosinusitis. Issue 7 (11th May 2017) - Barham, Henry P.; Zhang, Alexander S.; Christensen, Jenna M.; Sacks, Raymond; Harvey, Richard J.
Abstract : Background: Episodic or recurrent sinonasal symptoms are often suspected as "sinus" in origin. With normal sinus radiology between events, the diagnosis of recurrent acute rhinosinusitis (RecARS) is made. However, other conditions can produce episodic symptoms. In this study we analyze acutely performed computed tomography (CT) in a population with suspected or self‐diagnosed "sinus" disease. Methods: Patients referred to a tertiary clinic for suspected RecARS were assessed. Sinus changes were defined by CT (initial assessment) and during the acute event, by a semiurgent CT performed during the symptomatic episode. Mucosal thickening, ostiomeatal compromise, and severe septal deformity were recorded. Symptom profile was assessed during both time‐points with the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). Results: Forty‐eight patients (49.5 ± 14.7 years of age, 70.8% female) were assessed. At presentation, 75% were resolute in a diagnosis of "sinus." Baseline Lund‐Mackay scores were <6 (median 0 [interquartile range 1]). Ostiomeatal compromise was 6.8% left and 4.5% right at baseline. Of the patients who returned for acute CT (n = 27), SNOT‐22 and subdomains were similar to baseline. Septal deviation was similar (13.6% vs 15.3%). Acutely, ostiomeatal compromise was 0% left and 7.4% right (n = 2). Of these 2 patients with ostiomeatal compromise, 1 was diagnosed with RecARS (4%) and the other with triptan‐responsive migraine, with incidental sinus changes. Final diagnosis was rhinitis (47%), headache/migraine (37%), and facial pain otherwise undefined (12.5%). Conclusion: Patients with a history of "recurrent acute sinusitis" and normal CT scans between episodes rarely have abnormal CT findings during acute exacerbations of symptoms. Antibiotics and surgical intervention are often inappropriate in this population.